2010
DOI: 10.1007/s12565-010-0072-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the ramification patterns of the subclavian branches as the subclavian artery passes in front or behind the scalenus anterior muscle

Abstract: We investigated the ramification patterns of four subclavian branches (i.e., vertebral artery, internal thoracic artery, thyrocervical trunk, and costocervical trunk) as the subclavian artery passes in front or behind the scalenus anterior muscle. The investigation was carried out on 56 cadavers (112 cases) during student dissection practice sessions at Osaka Dental University. In 110 of the 112 cases, the subclavian artery passed behind the scalenus anterior muscle. The pattern of ramification of the subclavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…This incidence of 100% was compared with previous studies as shown in Table 3 . Other abnormal origins as observed by Daseler and Anson [ 12 ], Henriquez-Pino et al [ 13 ], Vorster et al [ 14 ], Uemura et al [ 15 ], and Karaman et al [ 5 ] were not observed in our study.…”
Section: Discussionsupporting
confidence: 59%
“…This incidence of 100% was compared with previous studies as shown in Table 3 . Other abnormal origins as observed by Daseler and Anson [ 12 ], Henriquez-Pino et al [ 13 ], Vorster et al [ 14 ], Uemura et al [ 15 ], and Karaman et al [ 5 ] were not observed in our study.…”
Section: Discussionsupporting
confidence: 59%
“…3,7,9 Variations in the course and branching of the subclavian artery have been reported to accompany the presence of SMM. 10,11 However, in our series, the subclavian artery had a typical course behind the anterior scalene muscle and in front of the SMM. It passed over the superior surface of the first rib and its branching followed the typical anatomical pattern.…”
Section: Discussionmentioning
confidence: 47%
“…Nidhi Puri et al reported in their study that a common trunk gives rise to ITA with other branches of subclavian artery in 12% on right side and 4% on left side [7]. A study on pattern of ramification of the subclavian artery in 56 cadavers (112 sides) reported that subclavian artery lying in front of the scalenus anterior muscle (3.5%) and also stated that the ITA originated from the TCT in 11.8 % of cases [8]. Lischka et al [9] mentioned in their study that the left ITA originated from the TCT in 10% of his cases, while the right ITA had the similar origin only in 2 %.…”
Section: Resultsmentioning
confidence: 96%